Development of E-Commerce Applications to Support Digital-Based Marketing - John Friadi; Angelina E. Rumengan; Dodi P. Yani; Muhamad Sigid Safarudin; Suroto Suroto (International Journal of Artificial Intelligence Research, 2022)
E-commerce is one of the application platforms that support digital-based marketing. The development of e-commerce from year to year is increasing, which is influenced by the development of information technology and the internet. The development of the internet has caused a shift in human activities from offline to online. During the Covid 19 pandemic, the growth of e-commerce has also increased sharply. The Covid 19 pandemic has caused a shift in human habits in purchasing goods from offline to online. This research develops a prototype e-commerce application to support digital-based marketing and conducts usability testing of the developed application using the SUS (System Usability Scale) scale. Based on the analysis and calculation of the SUS scale score, a score of 77.03 is obtained, meaning that the application is functionally good and acceptable to users and shows that using e-commerce applications supports digital-based marketing and affects the increase in marketing and sales